2022
DOI: 10.1017/s0954102022000086
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the suitability of Branchinecta gaini as a potential biomonitor of contaminants of emerging concern in the Antarctic Peninsula region

Abstract: The occurrence and impact of contaminants of emerging concerns (CECs) have been investigated in Antarctica much less than in other parts of the world. Although legacy anthropogenic pollutants can reach Antarctica via long-range transport, CECs mainly originate from local sources. Here, we investigated the ability of a freshwater crustacean, the Antarctic fairy shrimp Branchinecta gaini, to cope with nanoscale titanium dioxide (n-TiO2), a widely used pigment in consumer products (e.g. paintings), including thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The characterization analysis confirmed the agglomeration behaviour of n-TiO 2 in high ionic strength media, with an average hydrodynamic size of 872.9 ± 73.8 nm in NSW and a weak negatively surface charge (-11.7 ± 0.7 mV). We previously reported instability and large agglomeration of n-TiO 2 (25 nm, anatase, from Sigma-Aldrich) in Antarctic rock pool waters (González-aravena et al, 2022) and our results are in line with previous studies in seawaters for this NP (reviewed in Corsi et al, 2020Corsi et al, , 2021. For example, Della Torre et al ( 2015) reported the formation of micrometric agglomerates (~970 nm) in artificial sea water for the same n-TiO 2 (Aeroxide © P25) at 10 µg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…The characterization analysis confirmed the agglomeration behaviour of n-TiO 2 in high ionic strength media, with an average hydrodynamic size of 872.9 ± 73.8 nm in NSW and a weak negatively surface charge (-11.7 ± 0.7 mV). We previously reported instability and large agglomeration of n-TiO 2 (25 nm, anatase, from Sigma-Aldrich) in Antarctic rock pool waters (González-aravena et al, 2022) and our results are in line with previous studies in seawaters for this NP (reviewed in Corsi et al, 2020Corsi et al, , 2021. For example, Della Torre et al ( 2015) reported the formation of micrometric agglomerates (~970 nm) in artificial sea water for the same n-TiO 2 (Aeroxide © P25) at 10 µg/mL.…”
Section: Resultsmentioning
confidence: 99%